Correlation between Surgical Procedure, Type of Surgery, Duration of Surgery, and Intraoperative Complications with the Usage of PICU - Rangan, Andy A.; Lampus, Harsali; Candy, Candy; Langi, Fima L. F. G. (Medical Scope Journal, 2026)
Abstract: Pediatric postoperative intensive care remains a topic of debate due to the high demand and limited availability of PICU beds. This study aimed to bridge that gap by identifying types of procedure (major or minor), emergency or elective surgery, type of duration and complication contributing to PICU admissions, thereby enhancing perioperative care quality and resource allocation. This was a prospective cohort study conducted at Prof. Dr. R. D. Kandou General Hospital Manado between August 2022 and December 2023 using pediatric patients undergoing surgery. Data were extracted from medical records, analyzed and evaluated using descriptive statistics, chi-square tests, and logistic regression. A p-value of <0.05 was considered statistically significant. The results showed that among 455 pediatric postoperative cases, 14% required PICU care. Emergency surgeries (57%), major procedures (87%), prolonged surgery (67%), intraoperative complications (7%), and preoperative PICU recommendations (42%) were associated with more PICU admissions. The significant key predictors were emergency surgery (p<0.001), intraoperative complications (p=0.005), and preoperative PICU recommendations (p<0.001). In conclusion, emergency surgeries, major procedures, prolonged surgery, and intraoperative complications are key determinants of PICU admissions in pediatric patients. Preoperative PICU recommendations were the strongest predictor of postoperative intensive care needs, followed by intraoperation complication and emergency operation. These highlight the need for improved preoperative assessment, perioperative risk stratification, and structured postoperative care planning to optimize PICU resource allocation and reduce unplanned admissions. Keywords: pediatric surgery; PICU admission; postoperative care; emergency surgery; risk factors; perioperative management